Peer‐assisted learning in medical education: A systematic review and meta‐analysis. Issue 4 (24th October 2021) - Brierley, Clarissa; Ellis, Leila; Reid, Emily Roisin
Abstract: Objectives: The prevalence of peer‐assisted learning (PAL) featuring alongside the core medical curriculum is increasing; however, the evidence base for PAL's efficacy on academic performance is limited. This systematic review of randomised studies of PAL in medical school sets out to assess the impact of PAL on academic outcomes in medical school and evaluate whether PAL confers a benefit in specific educational contexts. Methods: A literature search was conducted across MEDLINE, Ovid Embase, Web of Science and Education Research Complete. Titles and abstracts were screened, and records were selected following strict eligibility criteria. Following full‐text assessment for eligibility, two reviewers independently extracted data from the final selection of records and a meta‐analysis was performed. Studies were classified using a modified version of Kirkpatrick's levels of learning. Student test scores were standardised by calculating the standardised mean difference (SMD). Results: Twenty‐seven randomised controlled trials were eligible for inclusion, and twenty‐one provided sufficient and complete data to enable meta‐analysis. There was a significant improvement in the academic performance of medical students who received PAL compared with those in the control group (SMD = 0.52 [95% confidence interval 0.18–0.85]; p  = .003). The impact of PAL was greater amongst clinical medical students (SMD = 0.63; p  = .02) than preclinical medical students (SMD = 0.39; p  = .08) and when used for teaching practical skills (SMD = 0.69; p  = .001) compared with theory (SMD = −0.11; p  = .21). Students taught by PAL also achieved better results in assessments conducted more than four weeks after course completion (SMD = 1.20; p  = .04). [Correction added on 8 November 2020 after first publication. The data values in the Results section have been corrected in this version.] Conclusions: Medical students experiencing PAL benefit in terms of academic performance, relative to those not receiving PAL. PAL is of greatest value in the clinical stages of training and for practical skills. The long‐term outcomes of PAL remain a priority for future research. Abstract : Using a systematic review and meta‐analysis, the authors demonstrate that peer‐assisted learning's benefit to academic performance are sustained in the medium‐to‐long term.